Twelve-month prostate volume reduction after MRI-guided transurethral ultrasound ablation of the prostate - Bonekamp, David; Röthke, Matthias C.; Pahernik, Sascha; Hatiboglu, Gencay; Hohenfellner, Markus; Schlemmer, Heinz-Peter; Wolf, Maya Barbara (European radiology, 2019)
PurposeTo quantitatively assess 12-month prostate volume (PV) reduction based on T2-weighted MRI and immediate post-treatment contrast-enhanced MRI non-perfused volume (NPV), and to compare measurements with predictions of acute and delayed ablation volumes based on MR-thermometry (MR-t), in a central radiology review of the Phase I clinical trial of MRI-guided transurethral ultrasound ablation (TULSA) in patients with localized prostate cancer.Materials and methodsTreatment day MRI and 12-month follow-up MRI and biopsy were available for central radiology review in 29 of 30 patients from the published institutional review board-approved, prospective, multi-centre, single-arm Phase I clinical trial of TULSA. Viable PV at 12 months was measured as the remaining PV on T2-weighted MRI, less 12-month NPV, scaled by the fraction of fibrosis in 12-month biopsy cores. Reduction of viable PV was compared to predictions based on the fraction of the prostate covered by the MR-t derived acute thermal ablation volume (ATAV, 55°C isotherm), delayed thermal ablation volume (DTAV, 240 cumulative equivalent minutes at 43°C thermal dose isocontour) and treatment-day NPV. We also report linear and volumetric comparisons between metrics.ResultsAfter TULSA, the median 12-month reduction in viable PV was 88%. DTAV predicted a reduction of 90%. Treatment day NPV predicted only 53% volume reduction, and underestimated ATAV and DTAV by 36% and 51%.ConclusionQuantitative volumetry of the TULSA phase I MR and biopsy data identifies DTAV (240 CEM43 thermal dose boundary) as a useful predictor of viable prostate tissue reduction at 12 months. Immediate post-treatment NPV underestimates tissue ablation.Key Points • MRI-guided transurethral ultrasound ablation (TULSA) achieved an 88% reduction of viable prostate tissue volume at 12 months, in excellent agreement with expectation from thermal dose calculations. • Non-perfused volume on immediate post-treatment contrast-enhanced MRI represents only 64% of the acute thermal ablation volume (ATAV), and reports only 60% (53% instead of 88% achieved) of the reduction in viable prostate tissue volume at 12 months. • MR-thermometry-based predictions of 12-month prostate volume reduction based on 240 cumulative equivalent minute thermal dose volume are in excellent agreement with reduction in viable prostate tissue volume measured on pre- and 12-month post-treatment T2w-MRI.
Published online: 25 June 2018
Gesehen am 01.08.2019